2012
DOI: 10.1183/20734735.0021711
|View full text |Cite|
|
Sign up to set email alerts
|

Spirometry: step by step

Abstract: N To give an overview of what spirometry is, how to perform it and how to interpret it. N To discuss the quality criteria to produce acceptable and reproducible results. N To discuss the use of spirometry in the workplace. SummarySpirometry is easy to perform once trained and can be performed anywhere. It is useful for detecting early change and disease progression. Quality is important to ensure useful and reproducible results, otherwise results may be incorrectly interpreted. Training from a reputable centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 10 publications
0
99
0
3
Order By: Relevance
“…The age range of the patients was 19-75 years with an average age of 41 years. On doctor's suggestion, the patients go through the standard spirometry [17] to measure the FEV1 and FVC. Prior approval for recording was obtained from hospital ethics committee and consent for recording was taken from each subject.…”
Section: Datasetmentioning
confidence: 99%
“…The age range of the patients was 19-75 years with an average age of 41 years. On doctor's suggestion, the patients go through the standard spirometry [17] to measure the FEV1 and FVC. Prior approval for recording was obtained from hospital ethics committee and consent for recording was taken from each subject.…”
Section: Datasetmentioning
confidence: 99%
“…In the case of restrictive ventilator defects, the FEV 1 /FVC ratio remains normal or typically high with reduced FEV 1 as well as FVC. A reduced FVC ratio, along with a lower FEV 1 /FVC ratio, is an indicator of a mixed ventilator defect [24,25]. In the current study, spirometry results revealed that 44% of the respondents in the experimental group, and 73% of the subjects in the control group, had a normal ventilatory function.…”
Section: Resultsmentioning
confidence: 48%
“…What changed the initial diagnosis, there were the results of spirometrydespite that the values of spirometry parameters were within the normal range, the shape of the flow-volume curve was abnormal. Instead of characteristic concave shape of flow-volume curve for bronchial obstruction with reduced FEV 1 and reduced FEV 1 /FVC ratio [8], there was a plateau of forced expiratory flow with normal FEV 1 and decreased PEF. Such changes should alert to the possibility of central airway obstruction [9][10][11].…”
Section: Discussionmentioning
confidence: 90%